Deep visual proteomics reveals DNA replication stress as a hallmark of signet ring cell carcinoma - Sonja Kabatnik; Xiang Zheng; Georgios Pappas; Sophia Steigerwald; Matthew P. Padula; Matthias Mann (npj Precision Oncology)
Abstract Signet Ring Cell Carcinoma (SRCC) is a rare and highly malignant form of adenocarcinoma with increasing incidence and poor prognosis due to late diagnosis and limited treatment options. We employed Deep Visual Proteomics (DVP), which combines AI-directed cell segmentation and classification with laser microdissection and ultra-high sensitivity mass spectrometry, for cell-type-specific proteomic analysis of SRCC across the bladder, prostate, seminal vesicle, and a lymph node of a single patient. DVP identified significant alterations in DNA damage response (DDR) proteins, particularly within the ATR and mismatch repair (MMR) pathways, indicating replication stress as a crucial factor in SRCC mutagenicity. Additionally, we observed substantial enrichment of immune-related proteins, reflecting high levels of cytotoxic T lymphocyte infiltration and elevated PD-1 expression. These findings suggest that pembrolizumab immunotherapy may be more effective than conventional chemotherapy for this patient. Our results provide novel insights into the proteomic landscape of SRCC, identify potential targets, and open up for personalized therapeutic strategies in managing SRCC.